Comparison of Continuous Subcutaneous Insulin Infusion and Multiple Daily Injections in Pediatric Type 1 Diabetes: A Meta‐Analysis and Prospective Cohort Study - Wang, Xu; Zhao, Xue; Chen, Danrong; Zhang, Mingzhi; Gu, Wei (Frontiers in Endocrinology, 2021)
Background: The incidence of pediatric type 1 diabetes (T1D) is increasing worldwide, and the appropriate choice of therapy regimens is important for children, especially in developing countries with inadequate resources. Methods: We conducted a design combining meta-analysis and prospective cohort study. In meta-analysis, 14 studies involving 69085 TID cases reported glycosylated hemoglobin (HbA1c) levels, including 48363 multiple daily insulin injections therapy (MIT) and 20722 continuous subcutaneous insulin infusion (CSII). In our prospective cohort study, TID cases were recruited from a tertiary children’s hospital, and randomly divided into Group MIT and Group CSII. After the four-year follow-up, the effects of MDI (n=112) and CSII (n=76) therapy on glycemic control, long-term complications, as well as the growth and pubertal development were explored. Results: Compared to CSII in TID, HbA1c levels in MDI (WMD=0.21, 95%CI: 0.20 to 0.23) were increased significantly in meta-analysis. Among 188 clinical cases, mean age at recruitment was 7.55 (SD 2.91) years. Duration of TID was 4.23 (SD 2.61) years. 50.53% (n=95) of them were boys. The four-year follow-up showed that children’s HbA1c was 0.67 (95% CI -1.28, -0.05) % lower in children with CSII compared to children with MDI in multivariable regression models with adjustment for potential confounders (children’s age at follow-up, duration of TID, gender, birthweight, parity and delivery method). CSII was associated with 2.31 kg higher in children’s weight (95% CI 0.59, 4.04) in the adjusted model. No difference was found in peripheral nerve and fundus consequences as well as the status of obesity and thin and pubertal development between CSII and MIT. Conclusion: CSII might be associated with better glycemic control and better effect for children growth development. No higher risks of long-term complications and delayed pubertal development were observed in CSII. Our findings provided evidence for a better therapy regimen for T1D in children, nevertheless, they need to be validated by a larger sample size study.